Human Oligodendrocyte Myelination Potential; Relation to Age and Differentiation. Issue 2 (10th January 2022) - Luo, Julia Xiao Xuan; Cui, Qiao‐Ling; Yaqubi, Moein; Hall, Jeffery A.; Dudley, Roy; Srour, Myriam; Addour, Nassima; Jamann, Hélène; Larochelle, Catherine; Blain, Manon; Healy, Luke M.; Stratton, Jo Anne; et al.
Abstract : Objective: Myelin regeneration in the human central nervous system relies on progenitor cells within the tissue parenchyma, with possible contribution from previously myelinating oligodendrocytes (OLs). In multiple sclerosis, a demyelinating disorder, variables affecting remyelination efficiency include age, severity of initial injury, and progenitor cell properties. Our aim was to investigate the effects of age and differentiation on the myelination potential of human OL lineage cells. Methods: We derived viable primary OL lineage cells from surgical resections of pediatric and adult brain tissue. Ensheathment capacity using nanofiber assays and transcriptomic profiles from RNA sequencing were compared between A2B5+ antibody‐selected progenitors and mature OLs (non‐selected cells). Results: We demonstrate that pediatric progenitor and mature cells ensheathed nanofibers more robustly than did adult progenitor and mature cells, respectively. Within both age groups, the percentage of fibers ensheathed and ensheathment length per fiber were greater for A2B5+ progenitors. Gene expression of OL progenitor markers PDGFRA and PTPRZ1 were higher in A2B5+ versus A2B5− cells and in pediatric A2B5+ versus adult A2B5+ cells. The p38 MAP kinases and actin cytoskeleton‐associated pathways were upregulated in pediatric cells; both have been shown to regulate OL process outgrowth. Significant upregulation of "cell senescence" genes was detected in pediatric samples; this could reflect their role in development and the increased susceptibility of pediatric OLs to activating cell death responses to stress. Interpretation: Our findings identify specific biological pathways relevant to myelination that are differentially enriched in human pediatric and adult OL lineage cells and suggest potential targets for remyelination enhancing therapies. ANN NEUROL 2022;91:178–191